Micropropagation Of Artocarpus hetrophyllus Lamk. - Choy, Li Lee; Chan, Lai Keng (Incorporated Society of Planters, 2005)
A micropropanganda protocol of Artocarpus heterophyllus lamk (Moraceae) was succesfully established Aprical shoots from 12 year old. A heterophyllus tree were used as explain.